Catalytic anodes and processes for use in electro-chlorination
A catalytic anode with a ruthenium-tin-titanium metallurgical layer addresses the cost and durability issues of existing anodes by forming a crack-free, efficient, and cost-effective structure for electrochlorination systems.
Patent Information
- Application Number
- JP2024099008
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-09
AI Technical Summary
Existing catalytic anodes for electrochlorination systems are costly due to the use of significant amounts of noble metals like iridium and ruthenium, and suffer from durability issues such as mud cracking, leading to efficiency losses and reduced service life.
A catalytic anode structure with a metallurgical layer composed of ruthenium, tin, and titanium, applied using a specific process involving isopropanol and water solvents and heat treatment, forming a crack-free, agglomerated particle morphology that enhances mechanical adhesion and conductivity, reducing the need for expensive noble metals.
The anode achieves high catalytic activity, selectivity for chlorine evolution, and durability, with improved resistance to acid corrosion and lower overvoltages, extending operational life and reducing production costs.
Smart Images

Figure 2025003385000001 
Figure 2025003385000002 
Figure 2025003385000003
Abstract
Description
[Technical field]
[0001] The present invention relates to catalytic anodes for use in electrochlorination systems for producing chlorine from aqueous solutions containing chloride ions by a chlorine evolution reaction. Such chlorine generation systems are particularly useful in ballast water treatment systems and in the industrial treatment and purification of wastewater, such as industrial and municipal waters. They can also be used in the industrial production of chlorine, particularly in the chlor-alkali process. [Background technology]
[0002] The chlorine evolution reaction ("CER") is a well-known reaction in industrial chemistry and has found applications in both large-scale production of chlorine for capture and immediate application. In the chlor-alkali process, chlorine and sodium hydroxide are produced by electrolysis of aqueous sodium chloride solution, and the products are recovered for further industrial use. Chlorine is an effective biocide, and therefore electrochlorination systems are used independently for water purification based on the in situ generation of aqueous chlorine and its biocidal effect. Microbially contaminated water can be effectively treated by electrochlorination, which has applications in various scenarios, such as industrial wastewater and general water disinfection. In addition, an increasing number of ships are being equipped with on-board ballast water treatment systems to treat ballast tank water before discharge. Ships traveling long distances may introduce invasive aquatic organisms into local ecosystems by discharging ballast water collected in remote areas. Invasive invasive species can have a significant impact on local ecosystem balance. Ship-mounted generator-powered electrochlorination systems provide an effective and immediate solution to treat such water before discharge. Effective industrial use of electrochlorination systems and methods relies on electrolysis cells that can operate efficiently for extended periods of time. To promote chlorine production at the anode, it is common in the art to apply a catalytic coating to the electrolyte-facing surface of the anode to catalyze the chlorine evolution reaction. Such catalytic coatings typically contain significant amounts of one or more precious metals, the most commonly used of which are iridium and ruthenium, which add significant cost and complexity to anode manufacture. There remains a continuing need in the art for new catalytic anodes that can more cost-effectively meet the various technical considerations associated with industrial or municipal electrochlorination environments. When selecting a catalytic coating for an electrochlorination anode, various technical considerations must be taken into account.
[0003] First, the catalyst selected must be sufficiently selective to the chlorine evolution reaction to reduce efficiency losses resulting from the competing oxygen evolution reaction, which may otherwise occur at the anode due to the electrolysis of water in aqueous solution. Second, the catalyst coating must be durable enough to withstand long-term operation and the acidification of the electrolyte that may occur during electrochlorination. Durability also requires good mechanical adhesion between the catalyst and the anode substrate surface. Third, the anode coating should be highly conductive to improve electrical efficiency by avoiding the need for large overpotentials to drive the electrolysis cell. Indeed, it is clear that some overpotentials typically occur with efficiency losses in electrolysis cells, but a lower degree of overpotential provides an important relative efficiency gain, and maintaining a lower overpotential over long-term operation provides another relevant indicator of electrode durability and service life. The physical durability of the catalytic coating on the anode can be evaluated both by its performance in long-term tests and, most preferably, by examining its morphology with a scanning electron microscope. Indeed, catalytic anode coatings in the art typically exhibit an external surface morphology resembling a dry lake bed, with the appearance of fine sedimentary deposits widely interrupted by characteristic "mud cracks", as shown in Figure 1. These cracks create weaknesses in the catalytic layer, allowing electrolyte and reactive species to penetrate toward the anode's substrate, weakening the bond between the catalyst and the substrate and resulting in a degradation process in which the exposed composition corrodes. Typically, this results in a loss of electrical efficiency (e.g., as manifested by an increase in overpotential) and a loss of catalytic activity, reducing the useful life of the anode and leading to expensive replacement. Summary of the Invention
[0004] The catalyst obtainable by the method of the first aspect of the invention offers an advantageous balance of properties that address these technical requirements of such anodes while avoiding the need for significant amounts of expensive precious metals, particularly iridium. In particular, the catalyst-coated anode structures defined in the first aspect of the invention exhibit high catalytic activity and selectivity for the chlorine evolution reaction, excellent durability in terms of operational life and mechanical adhesion of the catalyst to the anode surface, and improved resistance to acids formed during operation. The catalyst-coated anode structures defined in the first aspect of the invention also have high anode conductivity, resulting in efficient electrical operation without excessive overpotentials that are maintained over long periods of operation.
[0005] These advantages of anodes fabricated according to the first aspect of the invention result from the presence of a conductive metallurgical layer of defined composition overlying the electrolyte-facing surface of the anode, which is best achieved by a preparation method employing control of reactants and process conditions as defined in the present invention. The present invention therefore provides in a first aspect a method for preparing a catalytic anode structure for use in an electrochlorination system, comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) providing on the electrolyte-facing surface of the substrate a conductive metallurgical composition (i), the composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 applying an electrically conductive metallurgical composition (i) comprising compounds of ruthenium, tin and titanium in an amount providing Including, the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450 ° C. A method is provided.
[0006] In the method of the first aspect of the invention, a catalytic anode structure for use in an electrochlorination system is prepared which comprises an electrically conductive solid substrate overlaid on its electrolyte-facing surface with an electrically conductive metallurgical layer, the layer having a morphology of agglomerated particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin and titanium, the ruthenium and tin being present in the metallurgical layer in amounts providing a total metal stoichiometry of Ru:Sn of 1:≧1 based on the total content of ruthenium and tin in the metallurgical layer. As used herein, the term "atomic % of the total metal atomic content" with respect to a particular metal in a composition refers to the number of atoms of that metal present in the relevant composition, expressed as a percentage of the total number of atoms of the metal element present in the relevant composition, regardless of whether such metal element is present in elemental form or in the form of a compound. As used herein, the term "overall metallic stoichiometric ratio" of a particular metallic element refers to the stoichiometric ratio of all atoms of such metallic element present in a composite metallurgical layer (or other composition, if applicable), regardless of whether such metallic element is present in elemental or compound form. For example, in a structure containing 15 atomic % ruthenium and 15 atomic % tin in pure elemental form, the overall metallic stoichiometric ratio of Ru:Sn is 15:15, i.e., 1:1, and in a structure containing 15 atomic % ruthenium in elemental ruthenium form, and 15 atomic % elemental tin and further compounded 15 atomic % tin in oxide form, the overall metallic stoichiometric ratio of Ru:Sn is 15:(15+15), i.e., 1:2.
[0007] The term "morphology" is used herein to describe the three-dimensional structure and appearance of the material in question. Morphology can be most usefully determined by scanning electron microscopy, as described herein below, which provides a three-dimensional image of the surface of the material so as to allow direct visual appreciation of its structure and appearance. The present invention is based in part on the discovery that an anode structure having superior properties for obtaining a CER reaction in electrochlorination can be advantageously obtained by the method of the present invention, which provides a metallurgical layer comprising tin in combination with ruthenium and titanium on the anode surface directly exposed to the electrolyte. The metallurgical layer on the anode provides the anode with a surface chemical composition and an advantageous morphology that achieves superior durability in terms of operating life and mechanical adhesion of the catalyst to the anode substrate, and provides advantageous catalytic activity and selectivity for the chlorine evolution reaction. The metallurgical layer also provides the anode with high resistance to acid corrosion and high conductivity, which translates into high electrical efficiency and long-term operating performance at low overpotentials. The use of tin in the structural base composition also makes it possible to achieve this anode performance at a significantly lower cost than conventional catalytic anodes based on iridium and / or large amounts of ruthenium as the main components.
[0008] In particular, the metallurgical layer composition essentially comprises a combination of ruthenium, tin, and titanium in the form of metal oxides, with the presence of a minimum percentage of ruthenium in combination with titanium, and the co-presence of tin in a stoichiometric amount equal to or exceeding the amount of ruthenium, providing a composition capable of forming structures having the morphology of agglomerated particles interspersed with voids, as further demonstrated herein below. In contrast to conventional thinking in the art regarding barrier layers, the particulate morphology of this composition contributes to improved mechanical adhesion of the metallurgical layer to the substrate, providing a highly adherent layer on the electrolyte-facing surface of the anode having a combination of properties favorable for the chlorine evolution reaction described above. The agglomerated particles on the outer surface of the morphological layer are also essential to provide a highly effective and available surface area for catalytic activity. In particular, this particulate morphology overcomes the mass transport limitations of conventional lake bed precipitate catalyst layers, allowing the catalytic anodes of the present invention to operate at higher efficiency with respect to the chlorine evolution reaction and contributing to their various advantages. The efficiency advantage in the chlorine evolution reaction of the catalytic anodes prepared by the method of the present invention is particularly exhibited by aqueous solutions of chloride ions having low salt levels (e.g., brine). The improved efficiency at low salt levels makes the electrode more suitable for a wide range of water treatment applications, such as municipal water applications or drinking water treatment, in addition to wastewater treatment and other chlorination applications. The improved efficiency also results in reduced levels of unwanted electrolysis by-products, such as chlorate and perchlorate ions. Formation of the catalytic anode structure is accomplished by a process of adding metallurgical layers under process conditions that are ideally favorable for the formation of the proper morphology of the composition. The process of the first embodiment is particularly characterized by the use of particular starting metallurgical compositions and preparation conditions that result in the desired anode structure.
[0009] First, starting composition (i) is provided with a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7The use of a conductive metallurgical composition (i) comprising compounds of ruthenium, tin, and titanium in amounts providing a metallurgical layer of the anode that provides advantageous catalytic performance under the process conditions of the present invention. The defined total metal stoichiometry of the starting composition (i) results in the desired morphology of the resulting layer, in particular a layer having a morphology of agglomerated particles interspersed with voids. This formation of the desired morphology is further promoted by the use of defined process solvents and, in some preferred embodiments, by heating the anode substrate to a temperature in the range of 50 to 200° C. during the application step (b). The use of a process solvent during application step (b) that is volatile under the conditions further allows for the formation of voids in the metallurgical layer. This solvent also results in the simultaneous loss of a certain proportion of the more volatile metal salts contained within the defined metallurgical content of starting composition (i), resulting in the formation of a metallurgical layer having a different total metal stoichiometry with respect to ruthenium, tin, and titanium than starting composition (i). It is believed that the use of a defined composition (i) and defined process conditions advantageously adjusts this simultaneous metal salt volatile loss, resulting in the formation of an applied metallurgical layer having a desired composition and morphology.
[0010] In a preferred embodiment, it has been found that the formation of the desired metallurgical layer on the anode is further enhanced by applying metallurgical composition (i) to a substrate that is heated to a specified temperature range of 50 to 200°C during the application step, and preferably throughout the application step. It has also been found that drying the resulting structure within the same temperature range of 50-200°C further enhances the formation of the desired metallurgical layer, particularly by favoring the formation of the desired morphology, a continuous layer uninterrupted by mud cracks or other significant through-hole discontinuities. Importantly, it has been found that a final heat treatment of the resulting structure at a temperature of at least 450°C is essential to enhance the formation of the desired metallurgical layer, in particular by favouring improved mechanical adhesion between the metallurgical layer and the anode substrate, and by favouring high selectivity for the chlorine evolution reaction over the oxygen evolution reaction via water splitting. In this regard, in the second aspect of the invention, a final heat treatment in the range of 450-600°C, and in particular an optimum final heat treatment at 500°C, is preferred, where higher selectivity for the chlorine evolution reaction and mechanical adhesion are observed. In the first aspect of the invention, the use of a specified process solvent for applying the metallurgical composition in step (b) is also essential, the process solvent being a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5, preferably in a volume ratio range of 82.5:17.5 to 87.5:12.5. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. It has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents in terms of the dissolving power of the starting compounds used in the method of the first aspect. In addition, it has been found that this composition of the process solvent is advantageous for the control of the surface morphology of the layer formed by the application of the metallurgical composition, both before and after the final heat treatment step, and in particular contributes to an agglomerated particulate morphology free of integrity weakening cracks. This ability to control the layer morphology is due in particular to the choice of alcohol and the alcohol to water ratio in the process solvent, the control being optimal at a volume ratio of 85:15 (isopropanol:water).
[0011] A further aspect of the invention is also described herein, which relates to an electrolytic process for catalytically generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the process of the second aspect, at which chlorine gas is generated from the aqueous solution at the anode. In a preferred embodiment of the electrolysis process, the chlorine gas generated by the process is used as a biocide to disinfect water, more particularly to disinfect ballast water, or industrial wastewater, or municipal or domestic water, such as recreational water for swimming pools and domestic drinking water. In an alternative preferred embodiment, the process is a chlor-alkali process for the production and recovery of chlorine. The invention will now be described in more detail as follows. This application includes the following figures: [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 illustrates a lake bed morphology of a conventional catalyst bed having extensive "mud cracks." [Figure 2-1] FIG. 2 shows the aggregated particulate morphology of the anode surface (comparative anode and anode of the present invention). [Figure 2-2] FIG. 2 shows the aggregated particulate morphology of the anode surface (comparative anode and anode of the present invention). [Diagram 3] FIG. 1 shows the effect of ruthenium stoichiometry in composition (i) of the method of the present invention on metallurgical layer durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] First aspect of the present invention (preparation method) A first aspect is a method for preparing a catalytic anode structure for use in an electrochlorination system, comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; and b) providing on the electrolyte-facing surface of the substrate a conductive metallurgical composition (i), the composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 applying an electrically conductive metallurgical composition (i) comprising compounds of ruthenium, tin, and titanium in amounts providing Including, the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450 ° C. A method is provided.
[0014] The method of the present invention results in a catalytic anode structure as defined below and is the preferred method for preparing anodes of this type. The temperature conditions and process solvents specified in the present method are important to obtain the desired catalytic anode structure. In this method, the obtained structure is heat-treated at a temperature in the range of at least 450° C., preferably in the range of 450° C. to 600° C., for example, 450° C. to 550° C. More preferably, the obtained structure is heat-treated at a temperature in the range of 475° C. to 525° C., and optimally at a temperature of 500° C. The method of the present invention also requires the use of a specified process solvent for applying the metallurgical composition in step (b), the process solvent being a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5, preferably in a volume ratio range of 82.5:17.5 to 87.5:12.5. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. It has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents in terms of the dissolving power of the starting compounds used in the method of the first aspect. In addition, it has been found that this composition of the process solvent is advantageous for controlling the surface morphology of the layer formed by application of the metallurgical composition, both before and after the final heat treatment step, and in particular contributes to the resulting metallurgical layer obtaining an agglomerated particulate morphology that is more preferably free of integrity-weakening cracks. This ability to control the layer morphology is due in particular to the choice of alcohol and the ratio of alcohol to water in the process solvent, with control being optimal at a volume ratio of 85:15 (isopropanol:water). Preferably, in the method of the present invention, the anode substrate (a) is heated to a temperature in the range of 55-200°C during step (b) and the resulting structure is then dried at a temperature in the same range. Preferably, heating of the anode substrate to this temperature range is carried out throughout step (b) and the resulting structure is then dried at a temperature in the same range. Optimally, the substrate (a) is heated to a temperature of 100°C throughout step (b) and the resulting structure is then dried at that temperature.
[0015] The use of a defined process solvent that is volatile under the conditions during application step (b) of the method, and heat treatment of the substrate, if present, allows for the formation of voids in the resulting metallurgical layer. In particular, it has been found that applying metallurgical composition (i) to a substrate which has preferably been heated in accordance with the second aspect of the invention enhances the formation of the desired metallurgical layer on the anode. Importantly, it has also been found that drying the resulting structure within the same temperature range enhances the formation of the desired metallurgical layer, in particular by favouring the formation of the desired morphology of a continuous layer, in particular a continuous layer uninterrupted by mud cracks or other significant through discontinuities. Importantly, it has been found that a required final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired metallurgical layer, particularly by promoting improved mechanical adhesion between the metallurgical layer and the anode substrate, and by promoting high selectivity for the chlorine evolution reaction over the oxygen evolution reaction via water splitting. In this regard, a final heat treatment in the range of 450-550°C, and especially an optimum final heat treatment at 500°C, is preferred in the process of the present invention, where higher selectivity for the chlorine evolution reaction and mechanical adhesion are observed. In the present method, the use of the temperature conditions and process solvents specified above, in combination with a starting composition (i) of specified metallurgical content, results in the formation on the anode substrate of a metallurgical layer having a desired composition and morphology suitable for use as a catalytic anode.
[0016] In the method of the first aspect, the composition (i) applied in step (b) comprises a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 The composition (i) comprises compounds of ruthenium, tin and titanium in amounts providing. Composition (i) is the starting composition of the metallurgical layer on the anode, and in the process of the present invention, it is important that the ruthenium content of composition (i) is at or above a level of 0.3 stoichiometrically relative to the tin and titanium present in the composition (corresponding to 30 atomic %) in order to reach the desired layer structure. It has been found that the durability of the resulting composition, when applied according to the process of the first aspect, is significantly improved when the ruthenium in the starting composition (i) is at or above this level. In addition, ruthenium promotes the overall conductivity of the composition. In this regard, the composition (i) applied in step (b) of the method may comprise a total metal stoichiometry of Ru 0.3 (Sn+Ti) 0.7 It is preferred that the composition (i) of the present invention contain an amount of ruthenium, tin, and titanium compound that provides a level of ruthenium that is optimal in composition (i) of the present process and is believed to result in a particularly efficient and durable anode structure.
[0017] The presence of a combination of tin and titanium in addition to ruthenium in composition (i) results in the formation of a metallurgical layer composition having the desired morphology of agglomerated particles and the absence of extensive mud cracking behavior seen in other compositions containing only ruthenium and titanium or only tin. In this regard, the minimum level of ruthenium relative to tin and titanium in starting composition (i) of 30 atomic % also leads, under the conditions of the present process, to the formation of a network of agglomerated particles in the resulting composition morphology and the absence of cracking behavior. The presence of tin in combination with ruthenium and titanium in composition (i) also contributes significantly to the long-term durability of anodes prepared according to the present method, providing increased mechanical adhesion between the metallurgical layer and the anode substrate. The tin content in composition (i) can be further adjusted to provide the resulting anode with the desired overall stoichiometric ratio of Ru:Sn in the final anode structure, and the desired performance in this regard. To optimize these benefits, it is preferred that tin and titanium are present in approximately equal amounts in composition (i). Thus, most preferably, composition (i) applied in step (b) contains a total metal stoichiometry of Ru in composition (i). 0.3 Sn ≧0.3 Ti ≦0.4 , optimally Ru 0.3 Sn 0.35 Ti 0.35 The present invention includes compounds of ruthenium, tin, and titanium in amounts providing In all the above embodiments of the method, in addition to the essential compounds of ruthenium, tin and titanium, trace amounts of other metal compounds may be present, but it is preferred that composition (i) consists essentially of compounds of ruthenium, tin and titanium, and preferably composition (i) contains a total metal stoichiometry of Ru. 0.3 (Sn+Ti) 0.7 , most preferably with a total metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 More preferably, the amount is in an amount that provides
[0018] In the method of the first aspect, a further metallurgical composition may be applied to the surface of the metallurgical layer resulting from the application of composition (i), for example as a supplemental catalyst composition for a particular application, provided that such supplemental composition does not interfere with the primary role and benefits of the layer resulting from the application of composition (i). Composition (i) for use in the process of the first aspect can be prepared from compounds known in the art for the purpose of metal oxide catalyst preparation and mixed together in the appropriate ratio in the presence of a process solvent in accordance with the teachings of the present invention. Such compounds can include related metal oxide compounds, allowing for better mixing or suspension, and where practical, typically other compounds are used that will be oxidized under subsequent heat treatment in the process to produce the desired metal oxide in situ. Thus, in the present process, the compounds of ruthenium, tin and titanium present in composition (i) preferably comprise compounds other than their respective oxide compounds, and the heated application in process step (b) followed by drying and heat treatment preferably thermally decomposes these compounds into one or more of the respective metal oxide or mixed metal oxide compounds within the composite metallurgical layer of the final anode structure. In this regard, the ruthenium, tin and titanium compounds present in composition (i) preferably comprise, and more preferably consist of, their respective halide or sulfate compounds, and / or complexes with acetylacetone, which provide suitable dispersion of the metals in the compositions used in the process and which are subsequently converted to their respective oxides under the conditions of the process of the invention to give rise to the desired anodes of the invention.
[0019] The starting composition (i) of the present process may further comprise other metal compounds that provide additional benefits to the resulting anode. Thus, the starting composition (i) may further comprise at least one palladium compound, preferably in an amount to provide a total palladium content of at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atom content of the starting composition. Composition (i) may further comprise at least one copper compound, or at least one aluminum compound, or at least one nickel compound, or more than one of the above, in an amount providing composition (i) with a total copper content of up to 10 atomic %, preferably up to 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of up to 30 atomic %, preferably up to 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of up to 15 atomic %, preferably up to 10 atomic %, based on the total metal atomic content of the composition, respectively. Composition (i) may further comprise at least one iridium compound in an amount providing a total iridium content of up to 15 atomic %, preferably up to 10 atomic %, respectively.
[0020] Such additional metallic species may be introduced via compounds thereof that are conventionally used in the art for inclusion in metallurgical coatings. In the method of the present invention, the conductive solid substrate consists essentially of a valve metal, preferably titanium, as detailed in the first aspect of the present invention. In the method of the present invention, the metallurgical composition applied in step (b) may be applied sequentially by coating techniques known in the art, such as brush application, roller application, or drawdown application, spray coating by means such as electrospray or pressure spray, dip coating, and curtain coating, where thicker coatings may be applied, if desired, by coating techniques that include multiple passes over the underlying structure. Preferably, the metallurgical compositions applied in step (b) are applied sequentially by brush coating in one or more passes over the underlying structure, or spray coating in one or more passes over the underlying structure, however, other conventional techniques can also be used to apply one or more of the metallurgical compositions.
[0021] The anode obtained by the method of the first aspect comprises an electrically conductive solid substrate having overlying on its surface facing the electrolyte a conductive catalytic metallurgical layer having the morphology of agglomerated particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin and titanium, the ruthenium and tin being present in the metallurgical layer in amounts providing a total metal stoichiometric ratio of Ru:Sn of 1:≧1 based on the total content of ruthenium and tin in the metallurgical layer. Such anode structures have the feature that the outer surface of the metallurgical layer has the morphology of agglomerated particles. The presence of occasional cracks or other surface discontinuities or fault lines is not excluded so long as such imperfections do not expose the underlying substrate to electrolytic corrosion. Preferably, however, the anode structures have a metallurgical layer with an outer surface morphology of a continuous, crack-free coating of agglomerated particles interspersed with voids that provide increased accessibility of the particles to the surface. The agglomerated particulate morphology of the outer surface of the metallurgical layer contrasts with the widespread crack-precipitate-like surface morphology of conventional catalytic anodes and can best be visualized by examination under a scanning electron microscope, as shown in the accompanying figures. In each case, scanning electron micrographs were obtained using a JSM-IT500 InTouchScope™ scanning electron microscope instrument, using the settings described in the associated figure legend.
[0022] In Figure 1, scanning electron microscopy of the exterior surface morphology of a conventional catalytic anode for electrochlorination reveals a characteristic "mud-crack" appearance with extensive deep cracks extending throughout the deposit-like surface coating. Such a morphology renders the catalytic surface susceptible to chemical attack, weakening its structural integrity and reducing its life and usefulness. In contrast, Figure 2 shows a characteristic surface, viewed by scanning electron microscopy at the indicated magnification, of a preferred catalytic anode comprising ruthenium, tin, and titanium, having a crack-free, agglomerated particulate morphology. For further comparison, the cracking characteristics of a conventional ruthenium and tin (dimensionally stable anode) composition are also shown. It is essential for the anode that ruthenium and tin are present in the metallurgical layer in amounts in combination with titanium to provide a total metal stoichiometric ratio of Ru:Sn of 1:≧1 based on the total content of ruthenium and tin in the metallurgical layer. An important finding of the present invention is the advantage of using a total stoichiometric amount of tin at least equivalent to the amount of ruthenium, which can significantly reduce the total ruthenium content of the electrode coating while also contributing to the advantageous combination of properties exhibited by the metallurgical layer of the present invention. In particular, the presence of the specified amount of tin promotes the mechanical integrity of the layer and its electrical conductivity. The total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the metallurgical layer is preferably 1:≧1.5, more preferably 1:≧2. Even more preferably, the total metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the metallurgical layer is 1:≧3, most preferably 1:≧5. The optimum value of this ratio in the present invention is in the range of 1:8 to 1:20, for example in the range of 1:8 to 1:15.
[0023] The individual metal contents and total metal stoichiometry of the composite metallurgical layer can be measured by known techniques using ICP-MS (Inductively Coupled Plasma Mass Spectroscopy) to determine the compositional characteristics of the present invention. Also, in all of the above embodiments of the anode resulting from the first aspect, the metallurgical layer may include a supplemental catalyst composition distributed on an upper surface and within the voids of the metallurgical layer, any such supplemental composition preferably being substantially free or free of any amount of precious metal oxides such as palladium or iridium other than those provided herein. Thus, the metallurgical layer may further comprise at least one palladium compound in an amount to provide a total palladium content of up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. The introduction of limited amounts of palladium into this layer is preferably achieved by including one or more palladium-based compounds in composition (i) or by subsequent doping. Small amounts of palladium provide an even further improvement in the efficiency of the chlorine evolution reaction, as evidenced by an increased low salt efficiency, particularly for water treatment applications. However, when the palladium content in the composition exceeds the upper limit of 7 atomic %, no further improvement in the efficiency of the chlorine generation reaction is achieved, as evidenced by no further increase in the low salt efficiency, particularly in the case of water treatment applications. For this reason, the palladium content associated with the cobalt oxide catalyst particles should be limited to the levels described in order to avoid unnecessary cost and complexity. It is preferred that the total palladium content is at most 5 atomic %, more preferably at most 3 atomic %, of the total metal atomic content of the metallurgical layer, and optimally, the total palladium content is at most 1.5% of the total metal atomic content of the metallurgical layer.
[0024] The anode of all the embodiments resulting from the first aspect essentially consists of a conductive solid substrate, which substrate is known in the art. This substrate preferably essentially consists of valve metals such as titanium, zirconium, niobium and tantalum (and alloys / mixtures containing these metals) and preferably titanium, most preferably titanium. Mixtures of valve metals may also be present in the substrate. Oxides of one or more valve metals essentially present in the substrate may be further observed or produced as artifacts under the conditions of anode manufacture and use, especially at the surface of the substrate or at the interface with the composite metallurgical layer, and their presence is not excluded from the substrate of the present invention, unless they form the main component of the substrate. Anode substrates can be produced by conventional means in the art, purchased or custom manufactured, and formed into any shape suitable for end use as an anode in an electrochemical cell or system. In particular, substrates can be formed into meshes, plates, and more complex three-dimensional shapes such as cylinders. Substrates may be coated on one or more sides with complex metallurgical layers depending on their design and configuration.
[0025] The metallurgical layer of all embodiments of the anode resulting from the method of the first aspect comprises metal oxide compounds of ruthenium, tin, and titanium, and preferably consists essentially of metal oxide compounds of ruthenium, tin, and titanium in the desired stoichiometric ratio of Ru:Sn. The combination of these three metals is important to obtain the correct morphology of the metallurgical layer composition in situ at the anode surface. Other metal oxides or other compounds may also be present as long as they do not adversely affect the morphology, but most preferably the composition consists of metal oxide compounds of ruthenium, tin, and titanium. In particular, certain combinations of ruthenium, tin, and titanium provide metallurgical layer compositions that exhibit desirable particulate morphology, resulting in resilient coatings that are resistant to significant cracking, and preferably free of cracking. In contrast, conventional coating compositions based on, for example, ruthenium and tin typically exhibit a precipitate-like "mud crack" surface (as shown in FIG. 2) and do not provide the same durability. Furthermore, the particular combination of ruthenium, tin, and titanium in the layer composition provides improved durability of the anode resulting from the first aspect of the invention compared to layer compositions containing only ruthenium and titanium, or only ruthenium and tin. In this regard, the combination of both tin and titanium with ruthenium provides the anode with improved anode life and improved mechanical adhesion, further contributing to the benefits of the invention.
[0026] When the process conditions of the first aspect of the invention are employed, the metal stoichiometry Ru ≧0.3 (Sn+Ti) ≦0.7 By applying a starting composition (1) having a stoichiometric level of at least 0.3, a suitable total stoichiometry of these metals in the metallurgical layer will be reached. With respect to the method of the first aspect, it is important that ruthenium is present in starting composition (i) at a stoichiometric level of at least 0.3 in order to obtain the anode and advantages of the present invention. However, one skilled in the art can vary this starting composition (i) within these limits to obtain a particular desired total metal stoichiometry. The above-described embodiments of the anode may include, in addition to the above-described features, one or more further components introduced by the method to enhance a particular property of the anode, so long as the overall advantages of the invention are still obtained. For example, in the method for preparing the anode structure of any preceding embodiment, composition (i) may further include a precious catalytic metal (in addition to any palladium, if present), preferably iridium, in the form of its oxide or other catalytically active species, in an amount that provides a total additional precious metal content, preferably an iridium content, of up to 15 atomic %, preferably up to 10 atomic %, more preferably up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. This optional presence of small amounts of precious metal, especially iridium, may be preferable in terms of further enhancing the catalytic performance of the anode, but should be limited according to the objective of the present invention to minimize the use of expensive precious metals. Thus, such amounts of precious metals are much less than the amounts typically used when the catalytic composition is based on such metals.
[0027] Alternatively or additionally, the anode metallurgical layer of all embodiments may further comprise at least one copper compound in an amount to provide in the metallurgical layer a total copper content of at most 10 atomic %, preferably at most 2 atomic %, of the total metal atomic content of the metallurgical layer; or at least one aluminum compound in an amount to provide in the layer a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, of the total metal atomic content of the metallurgical layer; or at least one nickel compound in an amount to provide in the layer a total aluminum content of at most 15 atomic %, preferably at most 10 atomic %, of the total metal atomic content of the metallurgical layer; or more than one of the above. The additional presence of copper, aluminum, or nickel in the metallurgical layer provides a further increase in catalyst selectivity for the chlorine evolution reaction, for example as measured by low salt efficiency.
[0028] Second aspect of the present invention (electrolysis method) In a second aspect, the present invention provides an electrolysis process for catalytically generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolysis cell comprising an electrolysis anode structure obtainable by the process of the first aspect, at which chlorine gas is generated from the aqueous solution at the anode. In a preferred embodiment of the electrolysis process embodiment, the chlorine gas generated by the process is used as a biocide to disinfect water, more particularly, ballast water, or industrial wastewater, or municipal or domestic water, such as recreational water for swimming pools and domestic drinking water. In an alternative preferred embodiment, the process is a chlor-alkali process for producing and recovering chlorine.
[0029] Exemplary embodiments of the present invention 1. Preparation Example Preparation of Exemplary Starting Compositions for the Methods of the Invention 1.A An exemplary starting composition (i) for use in step (b) of the present method was prepared from the following component compounds and liquids available in the art: Crystalline solid compounds: RuCl 3. xH2O (commercially available, obtained from Sigma-Aldrich), SnCl 4. 5H2O (commercially available, obtained from Sigma-Aldrich), SbCl3 (commercially available, obtained from Sigma-Aldrich), liquid: 2-propanol (also called isopropanol, commercially available and obtained from Alfa Aesar); Deionized water, TiCl3 solution (TiCl3 is commercially available and was obtained from Sigma-Aldrich and dissolved to a 12% solution in aqueous hydrochloric acid).
[0030] 1.B Preparation of the Starting Composition (i) of the Method A total metal stoichiometry of Ru for use in the present method to form a metallurgical layer.0.3 Sn 0.35 Ti 0.35 A preferred composition (i) consisting essentially of compounds of ruthenium, tin, and titanium having the formula: was prepared according to the following sequence: In a 70 mL vial, add RuCl3.xHO (207.6 mg; 1 mmol) and SnCl 4. 5H2O (409.4 mg; 1.17 mmol) was added. The solid material was dissolved in 2-propanol (17 ml) by vortexing until no metal precursor precipitated on standing. 1.5 ml of TiCl3 solution (12% TiCl3 in hydrochloric acid solution, 1.17 mmol) was added dropwise to the resulting solution with mechanical stirring at 1,000 rpm. Additionally, 1.5 ml of deionized water was added dropwise to the solution. The resulting solution was aged for 5 hours under ambient conditions with mechanical stirring at 1,000 rpm to produce composition (i) for use in the method of the present invention.
[0031] Preparation of catalytic anodes by the method of the present invention An anode was prepared according to the method of the first aspect of the invention as follows. A titanium mesh was prepared as an anode substrate, which was heated to a temperature of 100° C. using a heating plate after cleaning. At this temperature, the composition (i) prepared above was applied to the heated substrate surface by brush coating. The resulting coated sample was kept at 100° C. for 1 minute, the substrate was turned over, the back side was coated again, and the substrate was kept at 100° C. for 1 minute. The coated sample was then transferred to a 500° C. oven and kept there for 5 minutes. The coated sample was then returned to the 100° C. hot plate and the coating and heat treatment steps were repeated. This brush coating of the substrate surface with composition (i) was repeated four more times, resulting in a total of five brush passes over the surface to be coated. The dried resultant structure was then subjected to a final heat treatment in an oven at 500° C. for 1 hour, followed by slow cooling in the oven for 8 hours to obtain the anode structure of the present invention.
[0032] 2. Performance examples The performance and advantages of the anode of the present invention were demonstrated using the following experimental techniques. Chlorine Evolution Reaction (CER) Life Test: The faradaic efficiency (FE) of the electrolytic cell, measured periodically over long-term testing, provides an important indication of the life of the catalytic anode and therefore of the durability of the anode for the CER reaction. A rapid increase in FE is an indication of anode degradation and, in the case of durability for CER, indicates that a limit is being reached. An electrolytic cell with counter and working electrodes was constructed as described above. For purposes of accelerating the test, the working electrode (anode) was placed 1 cm 2 The area was masked to concentrate the current density. Masking was performed by applying a silicon tape and then applying an electroplating tape on top of it. In addition, before connecting, the top of the working electrode was polished back to the metal substrate. a) 1 liter of 0.6M NaCl solution was poured into a beaker surrounded by a cooling jacket, and the test solution was maintained at 15° C. After allowing the temperature to stabilize for 1 hour, the electrode cell assembled above was placed in the beaker, and two wires were connected to the working electrode and counter electrode, respectively. b) The solution was stirred at 300 rpm using a magnetic stir bar. The attached potentiostat was then turned on at 500 mA / cm under 300 rpm stirring. 2 The device was operated in chronopotentiometry mode until an increase of more than 12 V was recorded, which marked the duration of the experiment. c) During operation, the cell potential was repeatedly measured and plotted over time to report the CER potential over the life test duration and to identify the degradation point where the potential increased so rapidly that it exceeded the useful life of the anode (taken as the point where a voltage above 12V was recorded).
[0033] 2.1 Benefits of composition (i) of the invention The metallurgical layer of the anode may be formed in a method according to the first aspect of the invention by using composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7The importance of these defined features in the process of the present invention was demonstrated as follows. Figure 3 reports the results of CER life tests carried out according to the test method described above. In each case, the working electrode (the anode under test) was prepared similar to the preparation method shown in section 1 of the Examples. Three examples of this type were prepared by varying the amount of ruthenium added to composition (i) and maintaining a 1:1 stoichiometric ratio of the tin and titanium components as the balance of each composition. As shown in Figure 3, the CER lifetime results indicate that maintenance of low overpotentials for extended periods (corresponding to good lifetime catalytic performance of the anode) could not be achieved when ruthenium was present at stoichiometric levels below 0.3. Thus, a specified stoichiometry in which ruthenium is present at a stoichiometric level of at least 0.3 in composition (i) is necessary to avoid the layer composition from affecting the catalytic anode's efficiency and durability for the CER reaction in a weakened manner.
[0034] This ruthenium stoichiometry also ensures that the desired morphology of this composition is obtained as a layer of aggregated particles interspersed with voids. A ruthenium stoichiometry of 0.3 in composition (i) resulted in a structure that showed a well-defined crystalline structure by XPS and well-defined connected particles when imaged using SEM. SEM examination after application of the metallurgical coating also revealed extensive mud cracking on the precipitate-like outer surface of the anode coating in the case of the ruthenium / tin comparative layer composition, as shown in Figure 2. In contrast, the coating made with the ternary base composition of the method of the present invention exhibited a crack-free coating of agglomerated particles interspersed with voids.
Claims
1. A method for preparing a catalytic anode structure for use in an electrochlorination system comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; and b) providing on the electrolyte-facing surface of said substrate a conductive metallurgical composition (i), said composition (i) having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 applying an electrically conductive metallurgical composition (i) comprising compounds of ruthenium, tin, and titanium in an amount providing Including, the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450° C. method.
2. 2. The method of claim 1, wherein the substrate (a) is heated to a temperature in the range of 50-200° C. during step (b), and the resulting structure is then dried at a temperature in the same range.
3. 3. The method according to claim 1 or 2, wherein the substrate (a) is heated to a temperature of 100° C. throughout step (b) and the resulting structure is then dried at that temperature.
4. The method according to any one of claims 1 to 3, wherein after drying, the heat treatment temperature is in the range of 450 to 550°C.
5. The method according to any one of claims 1 to 4, wherein the heat treatment temperature is 500°C.
6. 6. The method of any one of claims 1 to 5, wherein the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 85:
15.
7. 7. The method of any one of claims 1 to 6, wherein the metallurgical composition applied in steps is applied sequentially by brush coating in one or more passes over the underlying structure.
8. 7. The method of any one of claims 1 to 6, wherein the metallurgical compositions applied in step (b) are applied sequentially by spray coating in one or more passes over the underlying structure.
9. The composition (i) applied in step (b) comprises a total metal stoichiometry of Ru 0.3 (Sn+Ti) 0.70 The method of any one of claims 1 to 8, comprising the compounds of ruthenium, tin and titanium in amounts providing
10. The composition (i) applied in step (b) comprises a total metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 10. The method of claim 9, comprising the compounds of ruthenium, tin, and titanium in amounts providing
11. 11. The method according to any one of claims 1 to 10, wherein composition (i) further comprises at least one palladium compound in an amount providing composition (i) with a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of composition (i).
12. 12. A method according to any one of claims 1 to 11, wherein the compounds of ruthenium, tin and titanium present in composition (i) each comprise compounds other than oxide compounds, and wherein heat treatment thereof and, if present, application of heat thereto in step (b) thermally decomposes these compounds into one or more of their respective metal oxide or mixed metal oxide compounds within the metallurgical layer of the final anode structure.
13. 13. The method of claim 12, wherein the compounds of ruthenium, tin and titanium present in composition (i) preferably comprise, and more preferably consist of, their respective halide or sulfate compounds, and / or complexes with acetylacetone.
14. 14. The method of any one of claims 1 to 13, wherein composition (i) further comprises at least one copper compound, or at least one aluminum compound, or at least one nickel compound, or more than one of the above, in an amount to provide composition (i) with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of composition (i), or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of composition (iii), or a total nickel content of at most 10 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of composition (i).
15. 15. The method according to any one of claims 1 to 14, wherein said composition (i) further comprises at least one iridium compound in an amount providing a total iridium content of up to 15 atomic %, preferably up to 10 atomic %, respectively, based on the total metal atomic content of the composition.
16. A method according to any one of the preceding claims, wherein the conductive solid substrate consists essentially of a valve metal, preferably titanium.
17. A method for generating chlorine gas from an aqueous solution containing chlorine ions, comprising the steps of: (i) placing an anode structure prepared according to any one of claims 1 to 16 in an electrolysis cell containing an aqueous solution containing chloride ions; and (ii) passing a current through the electrolysis cell to generate chlorine gas from the aqueous solution at the anode; Electrolysis method comprising:
18. 20. The electrolysis process of claim 17, wherein the evolution of chlorine gas from the aqueous solution is facilitated by catalytic action of the metallurgical layer overlying a surface of the anode.
19. 19. The electrolytic process according to claim 17 or 18, wherein the chlorine gas generated by the process is used as a biocide for disinfecting water.
20. 20. The electrolysis method of claim 19, wherein the chlorine gas is used to disinfect ballast water or industrial or municipal wastewater.
21. 19. An electrolytic process according to claim 17 or 18, wherein the process is a chlor-alkali process for the production and recovery of chlorine.
22. Catalytic anode obtainable by the method according to any one of the preceding claims.
23. A catalytic anode obtainable by the method according to any one of claims 1 to 16.